Student’s Book Development Forcrafts and Entrepreneurship Subjects uses Creative Project-Based Learning Model - Miftahurrahmi Miftahurrahmi; Usmeldi Usmeldi; Nurhasan Syah (Postgraduate School, Universitas Negeri Padang, 2021)
This research purpose is to produce students’ books For Crafts And Entrepreneurship Subjectswhich are valid, practical, and effective. The design uses the Development method with a 4D model. The subjects were students of class XI MIPA 4 as the control class and students of class XI MIPA 2 as the experimental class at SMAN 4 Padang. Based on the results, Student’s Book Development For Crafts And Entrepreneurship Subjectsuses a valid, practical, and effective Creative Project-based Learning model to increase students' creativity. The student's book that was developed was validly reviewed by material experts and subject teachers. The developed student books are categorized as practical for use in the learning process obtained from the responses of teachers and students. The effectiveness can be seen from student learning activities, namely 92.02% in the category of many, the assessment of student skills with an average value of 87.62, and the assessment of student knowledge with an average assessment of 85.25 in the control class which is higher than the experimental class, which is 76, 41. So it can be concluded that the student's book for Crafts and Entrepreneurship Subjects uses a valid, practical, and effective Project-based learning model to increase students' creativity in learning.